A Case of Very Early‐Onset Crohn's Disease Presenting With Intractable Stomatitis and Cheilitis as Its Major Signs. Issue 2 (9th May 2018) - Saitoh, Issei; Kurosawa, Mie; Nagai, Haruka; Fujii, Toru; Aoyagi, You; Nakakura‐Ohshima, Kuniko; Iwase, Yoko; Hayasaki, Haruaki; Shirakawa, Tetsuo
Abstract : Background: Oral inflammatory lesions assist in the diagnosis of certain systemic diseases that primarily affect other organs. Methods: A young girl, 3 years and 3 months old, presented with aphthous stomatitis, upper lip cheilitis, and swelling and bleeding of the upper gingiva. She had a medical history of repeated fever, skin tag of the anus, and constipation. Thus, it was suspected that her disease is a systemic disease with digestive symptoms. From clinical manifestation and endoscopy findings containing aphthoid ulcers in the bowel, she was diagnosed with very early‐onset Crohn's disease (CD). Immediately, mesalazine was started. Results: After 1 month, the oral symptoms were dramatically improved, and her general condition stabilized. Conclusions: Oral symptoms often precede the appearance of gastrointestinal lesions in young CD patients, and oral conditions worsen if the disease remains untreated. Thus, assessment of patients with intractable stomatitis from the viewpoint of CD may aid in rapid diagnosis and better prognosis.